Evaluación de la sensibilidad de la cuota de los préstamos a interés variable a la variación del índice de referencia: Evidencia empírica en el mercado hipotecario espa\~nol en el periodo 2009-2013 - Jorge de Andrés Sánchez (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2015)
– In adjustable interest loans the borrower assumes the risk of interest rate rising, which leads to the growth of loan annuities. Given the importance of this risk in both corporate and personal finance, it is a recurrent topic in economic and financial press. In this paper, we show that the duration of a loan with constant annuity and interest rate can be used to assess the sensitivity of payments of an analogous loan with adjustable interest rate. Also, we develop an empirical application on official indexes of the Spanish mortgage market during the period 2009-2013. We find that EURIBOR is the index that causes less volatility in the mortgage annuity. Likewise, we also obtain that the average rate of loans for house purchasing in the euro zone is the index that cause greater volatility in the payments of loans.
Keywords: D14; G12; G21; 330; Adjustable rate loans; Postpayable amortization; Constant annuity loan; Duration; Indexes of the Spanish mortgage market